2003
DOI: 10.1152/ajpheart.01146.2002
|View full text |Cite
|
Sign up to set email alerts
|

CD117+ stem cells play a key role in therapeutic angiogenesis induced by bone marrow cell implantation

Abstract: Therapeutic angiogenesis can be induced by the implantation of bone marrow mononuclear cells. We investigated the roles of mature mononuclear cell and stem cell fractions in bone marrow in this treatment. Although CD34 is the most popular marker for stem cell selection for inducing therapeutic angiogenesis, we separated CD117-positive cells (CD117+) from mature bone marrow mononuclear cells [CD117-negative cells (CD117–)] from mice using the antibody to the stem cell receptor, because some of the bone marrow s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 32 publications
3
88
1
3
Order By: Relevance
“…Although the intramyocardial implantation of CD117 ϩ /Lin Ϫ bone marrow stem cells can regenerate infarcted myocardium effectively, 7 we separated the total CD117 ϩ bone marrow stem cells, because more than 80% of the separated CD117 ϩ cells are lineage-negative, and the remaining CD117 ϩ /Lin ϩ cells are considered a valuable subpopulation for inducing angiogenesis to improve regional perfusion in the infarcted myocardium. 14 In fact, the significant increase in microvessel density in our preprogrammed and untreated groups clearly demonstrated that the implantation of CD117 ϩ stem cells into the infarcted myocardium has the potential to induce therapeutic angiogenesis. This significant increase in microvessel density in both the preprogrammed and untreated groups contributed, at least in part, to ).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although the intramyocardial implantation of CD117 ϩ /Lin Ϫ bone marrow stem cells can regenerate infarcted myocardium effectively, 7 we separated the total CD117 ϩ bone marrow stem cells, because more than 80% of the separated CD117 ϩ cells are lineage-negative, and the remaining CD117 ϩ /Lin ϩ cells are considered a valuable subpopulation for inducing angiogenesis to improve regional perfusion in the infarcted myocardium. 14 In fact, the significant increase in microvessel density in our preprogrammed and untreated groups clearly demonstrated that the implantation of CD117 ϩ stem cells into the infarcted myocardium has the potential to induce therapeutic angiogenesis. This significant increase in microvessel density in both the preprogrammed and untreated groups contributed, at least in part, to ).…”
Section: Discussionmentioning
confidence: 67%
“…14 Briefly, bone marrow mononuclear cells collected from the femur and tibia of mice were incubated with PE-conjugated anti-mouse CD117 (c-kit) antibody (Bioscience) for 30 minutes on ice. After washing with PBS, cells were incubated with anti-PE microbeads (Miltenyi Biotec) for 20 minutes.…”
Section: Isolation and Culture Of Bone Marrow-derived Cd117mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the isolated ad-MVF had a comparable average length and cellular composition. Of interest, the ad-MVF did not only contain CD31 + endothelial cells and α-SMA + perivascular cells, but also cells expressing the stem cell surface markers CD90 and CD117, which have been reported to exhibit a high regenerative and angiogenic potential (Li et al, 2003;Li et al, 2005;Oishi and Ito-Dufros, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…It is noteworthy that endothelial cells express c-kit whose importance in angiogenesis has been outlined. 2,3 Tateishi et al 1 have previously shown CD31 þ endothelial cells expressing Ki-67 in muscle samples of a CLI patient who died 3.2 months after implantation of BM-MNC, suggesting the presence of proliferating endothelial cells in newly formed vessels. The origin of these cells remains to be determined: did they belong to implanted cells?…”
mentioning
confidence: 99%